CSF Tau proteins reduce misdiagnosis of sporadic Creutzfeldt-Jakob disease suspected cases with inconclusive 14-3-3 result - Leitão, MJ (2016)
Cerebrospinal fluid (CSF) 14-3-3 protein supports sporadic Creutzfeldt-Jakob (sCJD) diagnosis, but often leads to weak-positive results and lacks standardization. In this study, we explored the added diagnostic value of Total Tau (t-Tau) and phosphorylated Tau (p-Tau) in sCJD diagnosis, particularly in the cases with inconclusive 14-3-3 result. 95 definite sCJD and 287 patients without prion disease (non-CJD) were included in this study. CSF samples were collected in routine clinical diagnosis and analysed for 14-3-3 detection by Western blot (WB). CSF t-Tau and p-Tau were quantified by commercial ELISA kits and PRNP and APOE genotyping assessed by PCR-RFLP. In a regression analysis of the whole cohort, 14-3-3 protein revealed an overall accuracy of 82 % (sensitivity = 96.7 %; specificity = 75.6 %) for sCJD. Regarding 14-3-3 clear positive results, we observed no added value either of t-Tau alone or p-Tau/t-Tau ratio in the model. On the other hand, considering 14-3-3 weak-positive cases, t-Tau protein increased the overall accuracy of 14-3-3 alone from 91 to 94 % and specificity from 74 to 93 % (p < 0.05), with no sensitivity improvement. However, inclusion of p-Tau/t-Tau ratio did not significantly improve the first model (p = 0.0595). Globally, t-Tau protein allowed a further discrimination of 65 % within 14-3-3 inconclusive results. Furthermore, PRNP MV genotype showed a trend to decrease 14-3-3 sensitivity (p = 0.051), but such effect was not seen on t-Tau protein. In light of these results, we suggest that t-Tau protein assay is of significant importance as a second marker in identifying 14-3-3 false-positive results among sCJD probable cases.